Analysis of The Human Capital, Economic Growth, and Education Spending on Poverty in Gowa District - Chairatul Djannah; Abd. Hamid Paddu; Anas Iswanto Anwar (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The research from this thesis aims to determine the extent of the effect of Human Capital, Economic Growth, and Education Expenditure on Poverty in Gowa Regency. In order to know how big the influence of Human Capital, Economic Growth, and Education Expenditure on Poverty in Gowa Regency, a multiple linear regression model is used with the ordinary least square method or the least squares method. The type of data in this study is secondary data, and based on the time dimension, namely time series data with a period from 2006 until 2020. The conclusion from this thesis show that the average length of schooling and economic growth have a positive influence on poverty in Gowa Regency. While, Education Expenditure has a negative effect to Poverty in Gowa Regency.